Advanced oxidation protein products in predicting acute kidney injury following cardiac surgery. (May 2015) - Du, Song-lin; Zeng, Xiang-zhen; Tian, Jian-wei; Ai, Jun; Wan, Jun; He, Jian-xing
Abstract To test the hypothesis whether serum advanced oxidation protein products (AOPP) are associated with increased acute kidney injury (AKI) after cardiopulmonary bypass (CPB) and could serve as a biomarker in this aspect, we performed a prospective cohort study. Thirty-five (22.3%) patients developed AKI, and 32 age- and gender-matched patients without AKI were selected as control. Serum AOPP 1 h after CPB were significantly higher among AKI patients compared with non-AKI patients (81.8 ± 18.6 versus 67.4 ± 12.5 μmol/L, p < 0.001), with an area under the receiver-operating characteristic (ROC) curve of 0.714. An optimal serum AOPP 1 h after CPB cutoff of 69.9 μmol/L had a sensitivity of 74%, specificity of 63% and a positive predictive value of 68% for predicting AKI. These results demonstrated that serum AOPP might be an early biomarker for AKI after CPB.